Search and Rescue System Based on NB-IoT Wearable Device - Christos Bouras; Apostolos Gkamas; Spyridon Katsampiris; Nikolaos Papachristos (Principles and Applications of Narrowband Internet of Things (NBIoT), IGI Global, 2020)
This chapter presents the design and development of a search and rescue (SAR) system, for the location and provision of aid to people who are missing or in imminent danger, especially those belonging to population groups with a particularly high probability of getting lost. With the use of Low-Power Wide Area Network (LPWAN) technology, such as Narrow Band Internet of Things (NB-IoΤ), authors are able to provide search and rescue solutions for individuals, especially those belonging to groups of people who are more likely to get lost. The central part of the system is a modular “wearable (portable)” device, while in the framework of the implementation of this system authors have seriously taken into consideration the aspects of energy efficiency in order to provide better battery life.